Autobiografia de uma escrita de ficção - Lima, Marilene Felinto Barbosa de (2019)
This work is a discussion on why writers of fiction write. It arose from a personal doubt of the author: on whether it is in the childhood of the writer that there is the birth of the impulse to write literature; I wonder if the act of playing in childhood leads to creative activity in adult life. The work has as object of investigation my own trajectory as a writer of fiction. It presents re-readings (or quasi-rewritten or simple clarifications) of seven short stories of fiction of my own, narratives that bring representations of childhood, and which served as a field of speculation in search of answers to questions such as: How did that specific experience (or content) appeared thus clad in one specific form? The work stands on the path taken by some writers who influenced me and who deal with similar issues. It also relies on the thought of scholars of the artistic subjectivity (philosophers, psychologists, language scholars, literature critics, among others). Finally, it makes a brief approach to the production of journalism as an example of nefarious activity and antagonistic to creation in literature